186k views
5 votes
How do you solve?

2z - 2z(1 + 3) = 48

User Jom George
by
5.3k points

1 Answer

6 votes

First, we want to distribute the 2z to what's in the parentheses:



2z-(2z+6z)=48


Then we need to distribute the negative sign outside of the parentheses in order to make it easier to solve and combine like terms:



2z-2z-6z=48


Now we combine like terms. The '2z' and '-2z' cancel each other out, so:



-6z=48


Then we solve for z by dividing by -6 on both sides:



z=-8


So now we know that z = -8.

User Tchoupi
by
6.0k points